INTEGRASI ILMU DAN AGAMA: PERSPEKTIF ISLAM DALAM ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI ILMU PENGETAHUAN - Abdul Hakim; Tobroni; Faridi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to explore the integration between science and religion in the context of Islam, focusing on three main aspects of the philosophy of science: ontology, epistemology, and axiology. The scope of the research includes the analysis of the relationship between scientific knowledge and Islamic teachings, as well as the development of educational models that integrate the two aspects. The method used is a qualitative approach through library research, which involves the analysis of Qur'anic texts, Hadiths, and classical works of scholars. The results of this study show that the integration of science and religion can enrich human understanding of reality and provide a clear direction in the development of ethical science. This study finds that the bayani, burhani, and irfani approaches complement each other in building a holistic science paradigm. The conclusion of this study confirms that the separation between science and religion must be avoided, as they are both integral parts of the search for truth. Thus, Islamic religious education (PAI) needs to play an active role in bridging these two fields to produce a generation that is intellectually intelligent and morally wise.